Jogo educativo adaptado a deficientes visuais - Santos Neto, José Belarmino dos (Universidade Federal Rural do Semi-Árido, 2019)
The issue of digital inclusion has sparked great debates in recent decades, and it is still one of society's most complex problems today. As the world population and its life expectancy increase, the number of people with some form of disability also tends to grow, and discussing this becomes of great importance because it’s necessary to think of ways to promote the welfare of individuals belonging to society in general, not excluding those who have the need for elements accessible to common or specific practices.The number of people with visual impairment is quite expressive, characterizing itself as one of the most common deficiencies in the world. The uses of the elements of technology are quite efficient and timely when used to aid the teaching and learning processes. Having this problem as a premise, this work seeks to foster the importance of digital inclusion of the visually impaired in the leisure and learning spaces, presenting the construction of the Blind Quiz; a digital, accessible and educational game for visually impaired children. The game was built to stimulate the accessible technological development and promote socialization among people with and without visual impairment, being based and motivated by experiences obtained in activities carried out with APAE students (Association of Parents and Friends of the Exceptional), in Pau dos Ferros . For the construction of the Blind Quiz, Godot Game Engine was used.
Monografia
Keywords: Inclusão digital; Deficiência visual; Jogos digitais; Blind Quiz; Digital Inclusion; Visual impairment; Digital games; CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO